Waist circumference as a screening tool for weight management: evaluation using receiver operating characteristic curves for Malay subjects - Moy, Foong Ming; Atiya, A.S. (SAGE Publications, 2003)
Body Mass Index (BMI) is the most established anthropometric indicator used for assessment of nutritional status. Other anthropometric indicators which are related closely to BMI are waist hip ratio (WHR) and waist circumference. In this paper, receiver operating characteristics (ROC) curves were constructed to assess the value of waist circumference and waist hip ratio as a screening measure for the need of weight management using BMI as the reference test. Sensitivity and specificity were calculated at several cut-offs. The areas under the ROC curve calculated by comparing waist circumference with BMI were high (0.70-0.86) while the areas calculated for WHR were low (0.46 -0.67). Sensitivities of 0.745 and 0.800 were observed at cut-off points of waist circumference at 90cm and 80cm for males and females respectively, while the false positive rates were 0.233 for males and 0.250 for females. These cut-off points could be considered as a fair trade-off. Therefore it is concluded that waist circumference performed better than WHR as a screening test. It is indicative that waist circumference could be used as a tool in raising awareness of weight management in this population.